QUALITY GUARANTEE SYSTEM IN CAHAYA UMMAT INTEGRATED ISLAMIC JUNIOR HIGH SCHOOL SEMARANG REGENCY - Nugroho, Pamuji Fitria; Sutarto, Joko; Rifai, Achmad (Educational Management, 2020)
Cahaya Ummat Integrated Islamic Junior High School is an educational unit that seeks to implement an Islamic education system. Based on observations and school quality report cards, the launching of the concept of quality assurance does not yet have the vision and direction for efforts to improve the quality culture, so that increasing the scale of quality and the development of stagnant education units tends to even decrease. The concept of this research aims to describe the efforts to guarantee the quality of education starting from the mapping, planning, organizing, implementing and monitoring stages. Education Quality is the level of conformity between the administration of educational units and national education standards. This research uses descriptive qualitative research design. Types and sources of data are primary and secondary data. The research data was obtained from the school management & community team and school documents, field observations and documentation. Data analysis techniques using the method of Miles and Huberman from data reduction, data presentation, and drawing conclusions / verification. The results showed the need for a quality assurance team was formed which mobilized all educational unit resources to focus on overseeing the quality assurance cycle in the educational unit.